Cover Image. (24th February 2022) - Steel, Zachary L.; Fogg, Alissa M.; Burnett, Ryan; Roberts, L. Jay; Safford, Hugh D.
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13281 "When bigger isn't better–Implications of large high‐severity wildfire patches for avian diversity and community composition" by Steel et al. Fire severity continuum in a dry conifer forest burned in the 2013 Rim Fire in the Sierra Nevada Mountains, USA. Photo credit: Ken Etzel.